The dynamic relationships between returns and financial performance of companies listed in Thailand Sustainability Investment (THSI) rated by Environment, Social and Governance - พานิช เรวดี (วารสารสังคมศาสตร์และมนุษยศาสตร์ สถาบันอุดมศึกษาเอกชนแห่งประเทศไทย, 2022)
This study examined the dynamic relationships between returns and financial performances of companies listed in Thailand Sustainability Investment (THSI) rated by Environment, Social and Governance. It investigated the relationships based on the Panel Data with the Fixed Effect Model. Then, the dynamic testing was implemented by the Panel Cointegration test, Panel VECM test, Panel Causality test, and Panel Impulse Response Function. The samples were 213 listed companies rated ESG. The financial performances studied were earning per share, net profit margin, debt-equity ratio, return on equity, return on asset, EBIT, dividend yield, book value per share, market value, assets, liabilities, and net profit from 1999 to 2021. The result showed that the average annual rate of return on securities prices depended on asset, liabilities, debt-equity ratio, return on assets, and book value per share. The average annual rate of return since 2014 increased by 0.7 percent from the previous year after the SET forced listed companies released its ESG ratings publicly. This policy implementation leads to a positive effect on the stock price. In addition, there were a long-term dynamic relationships among the studied variables.